PENGARUH JALAN TERHADAP KERAGAMAN JENIS TUMBUHAN BAWAH DAN HABITATNYA DI KORIDOR TAMAN NASIONAL GUNUNG HALIMUN SALAK, JAWA BARAT - Robiansyah, Iyan; Purnomo, Danang W. (JURNAL BIOLOGI INDONESIA, 2013)
The road across the forest can cause the diversity exchange in the forest ecosystem. Distribution of the exotic speciescaused by the road are the main factor affecting the extinction of the native plants. The forest corridor in HalimunSalak National Park is separated by the road which is connecting five villages in surroundings. The aims of the researchwere to determine the response of diversity and abundance of the understory plants to the road existence, toobtain the effect of the road to the habitat condition, and to identify the exotic plants and its relation to the road.Vegetations were observed by transect sampling system, 5 transects of 150 m length were placed in forest corridorside along the road. In each transect, there were 12 sampling plots (1m x 1m) placed in distance (from the road): 0,5, 10, 15, 20, 30, 40, 45, 60, 90, 120, and 150 m from the road. The distance of each transect was approximately100 m and each transect were placed in the corridor area having forest buffer about 100 m distance. There were 117plant species including 9 exotic species. Plant community analysis using Squared Euclidean Distance (SED) showedthat road side area to 5 m in distance showed the different composition of the understory plant to inside the forest.Exotic plants and grass dominated in the area close to the road. Canopy cover in the road side to 10 meter to theforest was relatively opened than inside the forest. Plant diversity analysis on both of all species and local speciesusing Canonical Correspondence Analysis (CCA) showed that species diversity of understory plants was notsignificantly affected by the distance from the road. Nevertheless, distance from the road was a main factorinfluencing the exotic species, while distance of 0 m showed the highest exotic plants diversity.Keywords: Corridor, exotic plant, Halimun Salak National Park, road, squared euclidean distance, understory plant